Peran Role Playing Dalam Meningkatkan Kreativitas Siswa Pada Pembelajaran Matematika Kelas VII Di SMPN 1 Sagaranten - Eti Robiatul Adawiah; Siti Qomariyah (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
Mathematics learning is seen as difficult and boring for students so students find it difficult to develop creativity in learning mathematics, so teachers are required to make changes to learning by applying more creative learning models. This is the background for the use of various learning models. This study aims to determine the role of role playing in increasing students' creativity in learning mathematics for class VII at SMPN 1 Sagaranten. This study used a qualitative descriptive analysis approach with Classroom Action Research (CAR). The results of this study are the application of the role playing learning model can make learning more interesting, the results of observations and class actions the creativity of class VII B students of SMPN 1 Sagaranten in mathematics learning varies, some increase and no, because not all students can carry out these roles properly and applying this role to the theme of discussing social arithmetic, there were still some students who felt shy and insecure in carrying out their roles so that even in calculations they were not too focused. However, the class situation becomes more interesting and active so that learning mathematics is carried out in a fun and without feeling, bored, drowsy or monotonous and also boring.